ANALISIS SENYAWA METABOLIK SEKUNDER DAUN CIPLUKAN DAN BUAH MAJA DALAM MENGHAMBAT PERKEMBANGAN HAMA SPODEPTERA EXIGUA PADA TANAMAN BAWANG - Desriani Desriani; Naeilul Chaeriah; Fitrawaty Orista Evar (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2026)
The purpose of this study was to determine the potential of the extract of the ciplukan leaf and Aegle marmelos as a botanical pesticide. To achieve this research objective, an analysis of the secondary metabolic content of the ciplukan and maja fruit plants was conducted with predetermined concentrations and percentages. Identification of secondary metabolite compounds of n-hexane extracts of ciplukan leaves and maja fruit using phytochemical tests consisting of alkaloid, flavonoid, tannin, saponin, and triterpenoid tests. Phytochemical screening was carried out to identify active ingredients in the form of secondary metabolites. These compounds can function as a plant defense mechanism against environmental stress, disease, and attack. The botanical insecticide from the combination of ciplukan leaves and maja fruit in the form of a liquid was filtered, after which a filtrate was obtained with a light brown to dark brown color. Phytochemical screening was carried out using a color test. The results of the study showed that based on the results of the phytochemical screening test, the secondary metabolic content of ciplukan leaves and maja fruit can be used as a botanical pesticide